2011
DOI: 10.1037/a0023426
|View full text |Cite
|
Sign up to set email alerts
|

Cohort differences in cognitive aging and terminal decline in the Seattle Longitudinal Study.

Abstract: Life span researchers have long been interested in how and why fundamental aspects of human ontogeny differ between cohorts of people who have lived through different historical epochs. When examined at the same age, later born cohorts are often cognitively and physically fitter than earlier born cohorts. Less is known, however, about cohort differences in the rate of cognitive aging and if, at the very end of life, pervasive mortality-related processes overshadow and minimize cohort differences. We used data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 92 publications
13
138
5
1
Order By: Relevance
“…To reconcile our findings with reports that secular advantages for later cohorts do not carry into late life (Gerstorf et al, 2011;Hülür et al, 2013), we heuristically sketch three scenarios for how cohort differences manifest in old age (Fries, 1980;Olshansky, Hayflick, & Carnes, 2002;Vaupel, 2010). The scenarios conjointly assume that (a) later-born cohorts live longer than earlier-born cohorts, (b) death late in life is preceded by a period of steep deterioration, and (c) average functioning at the time of death has not changed historically (i.e., people die at older ages, but are neither healthier nor sicker at death than before).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…To reconcile our findings with reports that secular advantages for later cohorts do not carry into late life (Gerstorf et al, 2011;Hülür et al, 2013), we heuristically sketch three scenarios for how cohort differences manifest in old age (Fries, 1980;Olshansky, Hayflick, & Carnes, 2002;Vaupel, 2010). The scenarios conjointly assume that (a) later-born cohorts live longer than earlier-born cohorts, (b) death late in life is preceded by a period of steep deterioration, and (c) average functioning at the time of death has not changed historically (i.e., people die at older ages, but are neither healthier nor sicker at death than before).…”
Section: Discussionsupporting
confidence: 64%
“…Secular increases favoring later-born cohorts in performance of adolescents and young adults on fluid intelligence measures have been widely documented (Flynn, 1999;Trahan, Stuebing, Fletcher, & Hiscock, 2014). Empirical studies have repeatedly shown that positive secular trends persist into late adulthood (Bowles, Grimm, & McArdle, 2005;Christensen et al, 2013;Finkel, Reynolds, McArdle, & Pedersen, 2007;Langa et al, 2008;Rönnlund & Nilsson, 2008;Schaie, Willis, & Pennak, 2005), but not up to the final years of old age (Gerstorf, Ram, Hoppmann, Willis, & Schaie, 2011;Hülür, Infurna, Ram, & Gerstorf, 2013). Adding to this body of research, with the current study, we have provided a comprehensive quantification of the nature and size of such trends in old age using data from participants residing in a narrowly defined geographical area.…”
mentioning
confidence: 99%
“…These associations are strongest in the age group up to about 75 years but tended to disappear in older populations (34,38) . Similar decreases of predictive power at higher age have been noted for other potential biomarkers (39,40) , although often there are not sufficient data on multiple age cohorts, especially the oldest old, available. Cohort and/or period effects may be partially responsible if there is a trend reversal or loss of predictive power at old age.…”
Section: Use Of Birth Cohorts For Biomarker Validationmentioning
confidence: 53%
“…Although measures of age-specific functioning based on disability may be biased by for instance social and cultural influences -which could potentially bias comparisons across cohorts and nations, also research based on objective measures of performance, including assessments of cognitive functioning based on standardized tests, show that there are in fact improvements across subsequent cohorts among those aged 50 and above (Skirbekk et al 2013;Gerstorf et al 2011). Such gains are likely to have taken place earlier in some countries than in others, partly as educational expansions have taken place at different periods which thereby could contribute to differences in in age-specific cognitive functioning across countries.…”
Section: Adding Education As a Demographic Dimension In Global Populamentioning
confidence: 99%